Protective effect of platelet-rich plasma on urethral injury model of male rats - YARAT, AYŞEN; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (WILEY, 2018)
Aims: Urethral stricture (US) formation is caused by fibrosis after excessive collagen formation following an injury or trauma to the urethra. In this study, we aimed to evaluate the effects of platelet-rich plasma (PRP) on a urethral injury (UI) model of male rats. Methods: A UI model was used by applying a coagulation current to the urethras of male rats. There were four groups with six rats in each: control group, PRP applied to naive urethra, UI group, and UI with PRP application. PRP was applied to the urethra after a coagulation current-induced injury as soon as possible. On the 14th day, all rats were sacrificed and urethral tissues were investigated for collagen type I, collagen type III, platelet-derived growth factor-alpha, platelet-derived growth factor-beta, and transforming growth factor-beta using quantitative real-time polymerase chain reaction and Western blot analysis. The effect of urethral damage and healing was evaluated for collagen type I-to-collagen type III ratio. Results: The collagen type I-to-collagen type III ratio was significantly higher in UI group (P < 0.05) than in the others, while UI with PRP application group had comparable results with the control group (P > 0.05). Conclusions: The results of this study show that PRP has a preventive effect on stricture formation in a UI model of rats, as shown by its effect on collagen synthesis. Further studies that eventually show the effects of PRP on human tissues are necessary and promising.
Keywords: collagen; fibrosis; injury; platelet-rich plasma; stricture; urethra; ACELLULAR MATRIX GRAFTS; FUNCTIONAL-EVALUATION; ANIMAL-MODEL; RECONSTRUCTION; STRICTURE; URETHROPLASTY; INJECTION; RABBIT; TISSUE